Η εικόνα ως πειραματική διάταξη της σχέσης ανάμεσα σε λεκτικό και ορατό - Συμεωνίδης, Θωμάς (Σύγκριση/Comparaison/Comparison, 2023)
My chosen title is indicative of my intention to examine the concept of the image as a dispositif that offers the possibilities for experimenting with the space and the language that concern the possibles relations between the sayable and the visible. My analysis will follow and reflect on the possibilities offered by conceptual innovations in the thought of Jacques Rancière and especially his proposed schema of transition from the representational to the aesthetic regime of art on the one hand, and the different regimes of imageness on the other. Experimentation with sense, space, aesthetic tissue and language can be summarized under the idea of the metamorphic processability of the image. In my paper, I am suggesting that this particular idea is possible due to a certain form of space and language, namely the space of the metaphorization of the word and the schematic language. Particularly critical in this context is the concept of the phrase-image, that is, a mechanism that carries two contrasting functions; one that generates phrases (connection) and one that inhibit their meaning (disconnection). With reference to contemporary artists such as Esther Shalev-Gerz, Alfredo Jaar, Sophie Ristelhueber, Raymond Depardon, the Portuguese director Pedro Costa, but also to more classical ones such as Gustave Flaubert, Robert Bresson and Jean-Luc Godard, my paper will support in an illustrative and concrete manner a grammar of experimentations and a typology of connections between saying and seeing that open up an aesthetic space of indistinction between word and image in contemporary art.